Bodies-territories and intersectionalities: contributions to public health surveillance - Coradin, Cristiane [UNESP]; Oliveira, Simone; Guevara, Maria de los Angeles Arias (My University, 2024)
Multiple bodies and territories expe-rience impacts, conflicts, and socioenvironmental injustices in different ways. The consequences of the neoextractivist accumulation patterns weigh differently on women, especially non-white wo-men. This text brings narratives of a wide range of women who live in different territories and expe-rience different impacts from major undertakin-gs. Through their narratives, we seek to unders-tand how they constitute their territorial bodies; how they are impacted; and how they resist colo-nialist domination, defend life, and restore heal-th. These impacts affect women’s means and ways of life, and restrict their ways of being, power, and knowledge in these territories, rendering them vulnerable, subject to the precariousness of life, immersed in systemic intoxication, reaching si-tuations classified as genocide. Faced with such threats, they manage collective resistance; trigger what makes them active subjectivity; and decolo-nize themselves as beings, knowledge, and power. In this way they defend life and restore their health and that of their environments. These experiences indicate ways to strengthen public health surveillance perspectives and networks.
Corpos-territórios e interseccionalidades: contribuições para uma vigilância popular em saúde
Keywords: Body-territory; Feminism; Political ecology; Public Health Surveillance; Socio-environmental conflicts